Medical Research Ethics: Challenges in the 21st Century - Zima, Tomas; Weisstub, David N. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book provides a current review of Medical Research Ethics on a global basis. The book contains chapters that are historically and philosophically reflective and aimed to promote a discussion about controversial and foundational aspects in the field. An elaborate group of chapters concentrates on key areas of medical research where there are core ethical issues that arise both in theory and practice: genetics, neuroscience, surgery, palliative care, diagnostics, risk and prediction, security, pandemic threats, finances, technology, and public policy.This book is suitable for use from the most basic introductory courses to the highest levels of expertise in multidisciplinary contexts. The insights and research by this group of top scholars in the field of bioethics is an indispensable read for medical students in bioethics seminars and courses as well as for philosophy of bioethics classes in departments of philosophy, nursing faculties, law schools where bioethics is linked to medical law, experts in comparative law and public health, international human rights, and is equally useful for policy planning in pharmaceutical companies.
Part 1: Philosophical Foundations -- Chapter 1. Embryo Research Ethics (Robert George) -- Chapter 2. The Ethics of Medical Research (David Novak) -- Chapter 3. Genopolitics (Jonathan Moreno) -- Part 2: Vulnerability -- Chapter 4. Persons and Groups: Protection of research participants with vulnerabilities as a process (Pawel Lukow) -- Chapter 5. Centring the Human Subject: Catalyzing Change in Ethics and Dementia Research (Susan Cox) -- Part 3: Genetics -- Chapter 6. Unproven Stem Cell-Based Interventions: Addressing Patients' Unmet Needs or Causing Patient Harms (Kirstin Matthews) -- Chapter 7. Genetic Privacy in the Age of Consumer & Forensic DNA Applications (Sheldon Krimsky) -- Part 4: Neuroscience -- Chapter 8. Ethical Issues in Neuroscience Research (Walter Glannon) -- Chapter 9. Should Prisoners' Participation in Neuroscientific Research Always be Disregarded When Making Decisions About Early Release? (Elizabeth Shaw) -- Chapter 10. Applying Neuroscience Research: The bioethical problems of predicting and explaining behavior (David Freedman) -- Chapter 11. Direct Benefit, Equipoise, And Research On The Non-Consenting (Stephen Napier) -- Part 5. Surgery -- Chapter 12. The Ethics of Surgical Research and Innovation (Wendy A Rogers) -- Part 6. Palliative Care -- Chapter 13. Opening Death's Door: Psilocybin and Therapeutic Meaning Response in Palliative Care (Duff Waring) -- Part 7. Diagnostics, Risk, and Prediction -- Chapter 14. How Risky Can Biomedical Research Be? (Joanna Rozynska) -- Chapter 15. Biomedical Ethics and Prediction of Terrorism (David Shapiro) -- Chapter 16. PTSD and Biomedical Research: Ethical Conundrums (Lenore Walker) -- Part 8. Security and Pandemic Threats -- Chapter 17. Human Rights and Priorities in Medical Research Ethics in Light of the COVID-19 Pandemic (Jonathan Hafetz) -- Chapter 18. An Aspirational Code of Conduct for Life Scientists (Malcolm Dando) -- Chapter 19. Research Ethics in Exceptional Times: What lessons should we learn from Covid-19? (Søren Holm) -- Chapter 20. Ethics of Expanded Access during the COVID-19 Pandemic (Eline Bunnik) -- Part 9. Research Ethics Review: Multicontinental Perspectives -- Chapter 21. Bioethics and its Relation to Medical Research in Japan: Historical Influences and Contemporary Pressures (Darryl Macer) -- Chapter 22. Ethical Evaluations of Clinical Trials in France: Towards European Standardization (Bettina Couderc) -- Chapter 23. Research Ethics and Research Ethics Committees in Europe (Dirk Lanzerath) -- Chapter 24. Conflicts of Interest in Biomedical Research in French Law (Guillaume Rousset) -- Part 10. Finances, Technology, and Public Policy -- Chapter 25. Structural Problems in the Practice of Psychiatric Research (Heather Stuart) -- Chapter 26. The Place of Digital and Artificial Intelligence in Medical Research (Anne-Marie Duguet) -- Chapter 27. A framework to govern the use of health data for research in Africa: A South African perspective (Ciara Staunton).
Keywords: Bioethics; Bioethics